Bartonella henselae Hepatic Abscesses and Associated Osteomyelitis in a Pediatric Patient - Molly Antonson; Lauren Klingemann; Kari Neemann (Case Reports in Infectious Diseases)
Bartonella henselae is a Gram-negative bacillus transmitted to humans via cat saliva or scratch. Cat scratch disease, the typical clinical manifestation of B. henselae infection, presents as localized cutaneous or regional lymphadenopathy. Rare, atypical presentations, generally reflecting bloodborne disseminated disease, can include hepatosplenic, cardiac, ocular, neurologic, or musculoskeletal involvement. Here, we present a case of disseminated B. henselae with hepatic abscesses and associated ischial osteomyelitis in an immunocompetent 2-year-old male patient. Although osteomyelitis is a rare manifestation of B. henselae infection, it should be included in the differential diagnosis in pediatric patients presenting with fever of unknown origin and musculoskeletal pain, especially in the setting of cat exposure. Hepatic involvement of B. henselae infection is associated with significant morbidity; therefore, abdominal imaging is critical in the diagnostic workup. This patient was successfully treated after a 6-week course of azithromycin and rifampin, as evidenced by symptom resolution and improved fluid collections on repeat imaging. While most cases of B. henselae resolve without treatment, in severe or disseminated infection such as this case, antibiotics such as azithromycin and rifampin should be considered for treatment.